الاحتياجات النفسية والاجتماعية لطلبة المرحلة الثانوية العائدين الى المدارس بعد كوفيد-19 - Asmaa Al-khtatneh (Penerbit USIM, 2024)
International Language and Education Conference 2021 (iLEC’21) e-PROCEEDINGS “Language and Education : New Morms” 2nd & 3rd November 2021 Organized by : Faculty of Major Language Studies (FPBU), USIM. Editor: Azalia Zaharuddin, Suhaili A. Jalil, Kirembwe Rashid Abdul Hameed, Wan Azura Wan Ahmad.